STRATEGIES AND ROLE OF LOCAL GOVERNMENT IN IMPROVING THE COMPETITIVENESS OF TRADITIONAL FISHERMEN IN PANDEGLANG, BANTEN - Kusumajanti Kusumajanti; Ni Putu Eka Widiastuti; Asep Kamaluddin (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2020)
The aims of study to explore in depth: a. strategies and role of local government supports the formation of fishermen groups and group performance in enhancing the competitiveness of traditional fishermen; b. Strategies undertaken by local governments to improve competitiveness so as to realize the prosperity of traditional fishermen, c. group communication model between local government, traditional fishermen group, and partners  This study use qualitative research methods with a critical paradigm referring to the critical concepts of Marxist thought. The results showed that the government through the Ministry of Marine Affairs and Fisheries Republic of Indonesia has issued Government Regulation no. 50 Year 2015 on empowering small fishermen and small fish farmers. The Ministry of Marine Affairs and Fisheries has an agenda to improve the welfare of traditional fishermen and to optimize their potentials in groups, which are handed down to the provincial and district fisheries departments. Pandeglang District Government as the object of research through Fisheries Department has the authority to manage, utilize, and conserve marine and fishery resources for the welfare of Pandeglang community, especially fisherman community, cultivation, processing and marketing of fish, and to increase contribution for PAD (District Owned Revenue). Fisheries Department develop strategies for improving the welfare of traditional fishermen, among others, encourage the formation of fishermen cooperatives with legal status. Socialization of the use of fishing gear which is not prohibited by the government. This is because there are still many traditional fishermen in Pandeglang who use Cantrang that can threaten the sustainability of marine ecosystems. The local government through related offices has not been actively involved in providing assistance to traditional fishermen so that they have high competitiveness such as maintaining good quality fish quality, stable catch quantity, environment of fishery and marine areas that is maintained so as to ensure the sustainability of existence fish in the sea. The results of this study have implications on the preparation of roles and strategies of local governments in improving the competitiveness of traditional fishermen adapted to local elements so that traditional fishermen become prosperous.